Literature Review: Model PRECEDE dapat Meningkatkan Kualitas Hidup Pasien dengan Coronary Artery Bypass Grafting (CABG) - Rahmawati, Lutfiasih; Anika, Lusi; Wicaksana, Anggi Lukman (Jurnal Kesehatan, 2021)
One type of cardiovascular disease that often occurs is coronary heart disease. Although the coronary artery bypass grafting (CABG) procedure can help overcome coronary heart disease problems, the post-CABG recovery stage can also lead to an increase in angina symptoms (chest pain), decreased ability to exercise, and mostly in the Quality of dimension life. The purpose of this literature review is to determine the effectiveness of the PRECEDE educational model in reducing depression and improving quality of life in patients with coronary heart disease who have CABG. This idea seems reasonable was carried out by searching through databases in PubMed and ScienceDirect until May 13, 2020, for nursing studies in chronic heart disease patients with CABG. Two articles were found that were suitable for a literature review. Findings from the literature suggest that designing educational interventions according to the PRECEDE model significantly improves all aspects of a patient's quality of life. Providing educational programs with the PRECEDE model can reduce depression in patients with CABG. This PRECEDE educational model can reduce depression and increase QoL in patients with Coronary heart disease who have undergone CABG.